What We Know about Student Families: A Sociological Analysis - K. A. Vilkova; I. A. Gruzdev; E. D. Shmeleva; E. A. Tarasova; S. V. Startsev (Высшее образование в России)
This study analyzes the phenomenon of student parents in Russia. The authors examine the demographic context, the characteristics of student parents, and their experience of combining study and parenthood. The study is based on data from the longitudinal project “Trajectories in Education and Profession” and in-depth interviews with student mothers. The results show that student families are relatively rare, which is in line with the general trend of increasing age of marriage and childbearing. Nevertheless, most students plan to start a family in the future. Students from families with lower socioeconomic background are more likely to start families during their studies. Analysis of the interviews revealed the main strategies for combining study and motherhood, including reorganization of daily routines, sabbaticals, and distance learning. The importance of support from partners and relatives was also noted. Student mothers expressed a demand for more flexible study formats, material support, and infrastructure development (e.g. kindergartens at universities). The authors conclude that an individualized approach to supporting student families is needed, given their rarity and diversity of needs. Directions for further research are suggested, including the study of social conditions influencing the age of family formation, analysis of family plans of older undergraduate and graduate students, and a more detailed study of the typology and daily life of student families.